Crosstalk between MicroRNAs and Peroxisome Proliferator-Activated Receptors and Their Emerging Regulatory Roles in Cardiovascular Pathophysiology - Yin-Feng Zhang; Hai-Ming Xu; Fei Yu; Man Wang; Meng-Yang Li; Tao Xu; Yan-Yan Gao; Jian-Xun Wang; Pei-Feng Li (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) play vital roles in cardiovascular pathophysiology, such as energy balance, cell proliferation/apoptosis, inflammatory response, and adipocyte differentiation. These vital roles make PPARs potential targets for therapeutic prevention of cardiovascular diseases (CVDs). Emerging evidence indicates that the crosstalk of microRNAs (miRNAs) and PPARs contributes greatly to CVD pathogenesis. PPARs are inhibited by miRNAs at posttranscriptional mechanisms in the progress of pulmonary hypertension and vascular dysfunction involving cell proliferation/apoptosis, communication, and normal function of endothelial cells and vascular smooth muscle cells. In the development of atherosclerosis and stroke, the activation of PPARs could change the transcripts of target miRNA through miRNA signalling. Furthermore, the mutual regulation of PPARs and miRNAs involves cell proliferation/apoptosis, cardiac remodeling, and dysfunction in heart diseases. In addition, obesity, an important cardiovascular risk, is modulated by the regulatory axis of PPARs/miRNAs, including adipogenesis, adipocyte dysfunction, insulin resistance, and macrophage polarization in adipose tissue. In this review, the crosstalk of PPARs and miRNAs and their emerging regulatory roles are summarized in the context of CVDs and risks. This provides an understanding of the underlying mechanism of the biological process related to CVD pathophysiology involving the interaction of PPARs and miRNAs and will lead to the development of PPARs/miRNAs as effective anti-CVD medications.